Peningkatan kompetensi Bahasa Inggris bagi Anggota Pokdarwis di Kampung Peneleh Surabaya - Rahmantyo, Lastiko Endi; Ahmad Syukri, Masitha; Salimah, Salimah (Eastasouth Institute, 2024)
Kampung Peneleh Surabaya is one of the tourist destinations that has the potential to become a heritage tourist destination for domestic or foreign tourists. Therefore, it is necessary to develop English language competence for tour guides who are members of the Kampung Peneleh Tourism Awareness Group (Pokdarwis). The plan of development is by conducting workshop for tour guides starting with Focus Group Discussions, making tourist destination guide scripts, and practice at the location. The result of this training is that Pokdarwis is very excited to take part in the training and from the evaluation results it is necessary to conduct further training to improve pronunciation, intonation, and fluency.